Value Co-creation in Global Channel Partnership Management: Applying Service-Dominant Logic in The Maritime Aftermarket - Nguyen, Thu (My University, 2026)
In recent years, in the maritime aftermarket, service delivery depends on distributed global partner networks. Companies have increasingly relied on global channel partners' capabilities, knowledge, and local presence to jointly deliver aftermarket services, products, and support customers over long product lifecycles. Thus, researchers and professionals are interested in how firms implement partner relationship management that enables value co-creation between organizations. This study aims to examine how partner relationship management enables value co-creation in global channel partnerships in the maritime aftermarket. This study draws on the understanding that a multinational maritime company desires to shape collaborative channel partnerships throughout the lifecycle of the partnership. This study employed a qualitative research approach. The main data was collected by semi-structured interviews. Five interviews were conducted with high-level managers in different countries of the case company and one of its partnering companies, all of whom were highly knowledgeable about partnership management within their respective organizations. The study analyzed the interview data by applying thematic analysis. The study provides insights into how value is co-created through service exchange in the maritime aftermarket sector, and what enables partners to co-create value with the manufacturer through contractual and relational governance mechanisms. Value is created through daily operations. However, because partner relationship management has not been structured yet, coordination activities are seen as reactive and value co-creation remains operational. Besides, the study found that limited shared digital tools, ambiguous internal ownership, and contract-focused governance reduce transparency, learning, visibility towards partners, and the ability to scale value co-creation across the global partner network. The empirical findings have challenged the initial framework. The study makes a contribution to the literature by extending service-dominant logic to the manufacturer-channel partners relationships in the maritime aftermarket sector and distinguishing between operational and strategic value co-creation. The revised framework highlights the role of onboarding, follow-up routines, performance evaluation, and internal operational factors in enabling resource integration and consistent value co-creation between partner organizations. The study’s insights offer guidance for multinational maritime companies to develop systematic approaches to manage channel partnerships across stages of the partnership lifecycle towards co-creation and collaboration between both sides.
Keywords: global channel partnerships; service-dominant logic; value co-creation; partner relationship management; channel partnership management; maritime aftermarket